The Manuzio Project - Mišetić, Marijana (Array, 2007)
The aim of this paper is to analyze the role of an academic library in the information society examining one of its old tasks, namely that to provide teaching and learning materials quickly and efficiently, now in an electronic environment. The analysis has been done in order to recognize the value and necessity of promotion of information literacy and e-texts by libraries, academic staff and university plans and programs. It has been done using the example of the Italian Studies Department Library, Faculty of Philosophy, University of Zagreb and is based on the library's experience in integrating new technologies in library services in order to remain relevant to the academic environment.